What Good Condition? Reflections on an Australian Aboriginal Treaty 1986-2006 - Read, Peter (Aboriginal History Monograph, 2006)
What Good Condition? collects edited papers, initially delivered at the Treaty Advancing Reconciliation conference, on the proposal for a treaty between Aboriginal and non-Aboriginal Australians, a proposal which has been discussed and dissected for nearly 30 years. Featuring contributions from prominent Aboriginal community leaders, legal experts and academics, this capacious work provides an overview of the context and legacy of the residue of treaty proposals and negotiations in past decades; a consideration of the implications of treaty in an Indigenous, national and international context; and, finally, some reflections on regional aspirations and achievements.